The Effect of Applying These Exercises is to Simulate Competition in Order to Develop Balance and Accuracy in the Numerical Combination Attack - Lafta, Zainab Nabil; Yasser, Ali Ammar; Makki, Haider Sadiq (JURNAL PENDIDIKAN OLAHRAGA, 2026)
The importance of this research lies in its contribution to enriching the scientific literature on the impact of applied exercises on developing fencing skills, and it opens avenues for similar studies in other sports. The research problem arose from the researcher's observation of a weakness in motor balance that may result from a lack of focus on exercises that simulate competition. This leads to difficulty maintaining the player's balance during the attack, increasing the risk of loss of control or injury. A lack of training that simulates competitive pressure can also affect the player's ability to deliver accurate jabs, reducing the effectiveness of numerical combination attacks. Furthermore, there is a lack of research... In terms of application, there is a limitation in studies that link practical, competition-simulating exercises with the specific improvement of fencing skills, making it difficult for coaches to design evidence-based training programs. Therefore, the researcher decided to study this problem to answer the main question: What is the effect of applying exercises that simulate competition on developing balance and accuracy of the numerical combined attack among students of the College of Physical Education and Sports Sciences? The two objectives of the research are to prepare applying exercises that simulate competition to develop balance and accuracy of the numerical combined attack, and to identify the statistical differences between the pre-tests. The researcher studied the lateral balance and accuracy of the combined numerical attack, and used the experimental method with a single group approach to suit the nature of the problem. The research population was determined purposively and consisted of fencing players in the (youth) category affiliated with the Ministry of Youth and Sports in Dhi Qar Governorate for the sports season (2024-2025), totaling Their number is (8) players, and they were chosen as a sample for research and they represent (100%) of the original community. One of the most important conclusions is that the exercises applied to simulate competition had an effect on developing balance for fencing players.